ANALYSIS OF VIBRATION CHARACTERISTICS ON WA-350 WHEEL LOADER HEAVY EQUIPMENT MACHINE BASED ON CAPACITY COMPARISON WITH 2000 RPM ROTATION IN HORIZONTAL, VERTICAL AND LONGITUDINAL AREAS - Sihombing, Suriady; Nababan, Wilson Sabastian; Tampubolon, Miduk; Panjaitan, Fernando (Jurnal Dinamika Vokasional Teknik Mesin, 2023)
Wheel loader is a tool that facilitates the work of moving materials from one place to another using hydraulic energy. Wheel loader machine testing is carried out by looking for vibration data arising in the engine block. There are several stages that must be done, the first step is preparation of a Handheld Vibrometer as a vibration detection device. Next, examine the vibration level read on the Handheld Vibrometer with ideal, medium, and maximum rotation. Based on the ISO 2372 standard, vibration response results are obtained where the power capacity of a diesel motor is 350 kW where the highest speed is 62.7 mm / s with a horizontal direction at 90 seconds, categorized in Zone D in red, vibration from the engine is within dangerous limits and can be damaged at any time.